Type 1 interferon signature in peripheral blood mononuclear cells and monocytes of idiopathic inflammatory myopathy patients with different myositis-specific autoantibodies - Li, Mengdi; Zhang, Yusheng; Zhang, Wenzhe; Sun, Jinlei; Liu, Rui; Pan, Zhou; Zhang, Panpan; Liu, Shengyun (Frontiers in Immunology, 2023)
Background Myositis-specific autoantibodies (MSAs) are clinically used to diagnose and define idiopathic inflammatory myopathy (IIM) subsets. However, the underlying pathogenic mechanisms of patients with different MSAs remain unclear. Methods A total of 158 Chinese patients with IIM and 167 gender- and age-matched healthy controls (HCs) were enrolled. Transcriptome sequencing (RNA-Seq) was performed with peripheral blood mononuclear cells (PBMCs), followed by the identification of differentially expressed genes (DEGs) and analysis of gene set enrichment analysis, immune cell infiltration, and WGCNA. Monocyte subsets and related cytokines/chemokines were quantified. The expressions of interferon (IFN)-related genes were validated using qRT-PCR and Western blot in both PBMCs and monocytes. We also performed correlation analysis and ROC analysis to explore the potential clinical significance of the IFN-related genes. Results There were 1,364 genes altered in patients with IIM, including 952 upregulated and 412 downregulated genes. The type I interferon (IFN-I) pathway was remarkably activated in patients with IIM. Compared with patients with other MSAs, IFN-I signatures were significantly activated in patients with anti-melanoma differentiation-associated gene 5 (MDA5) antibodies. In total, 1,288 hub genes associated with IIM onset were identified using WGCNA, including 29 key DEGs associated with IFN signaling. The patients had more CD14brightCD16- classical, CD14brightCD16+ intermediate, and fewer CD14dimCD16+ non-classical monocyte subsets. Plasma cytokines like IL-6 and TNF and chemokines including CCL3 and MCPs increased. The validation of IFN-I-related gene expressions was consistent with the findings from RNA-Seq. The IFN-related genes were correlated with laboratory parameters and helpful for IIM diagnosis. Conclusion Gene expressions were remarkably altered in the PBMCs of IIM patients. Anti-MDA5+ IIM patients had a more pronounced activated IFN signature than others. Monocytes exhibited a proinflammatory feature and contributed to the IFN signature of IIM patients.